Knowledge, attitude and practice on bats-borne diseases among village residents : a pilot study - Nurul Azmawati Mohamed,; Hariz MS,; Mohd Dzulkhairi MR,; Shalinawati R,; Ilina I, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Ebola virus disease (EVD), Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV), rabies and Nipah infections were examples of diseases that were related to bats and shook the world with a series of outbreak and epidemic. Through the understanding of bats as potential public health risk, awareness had become vital to prevent another outbreak. This pilot study was done to evaluate the appropriateness of the questionnaires and to determine preliminary data on knowledge, attitude and practices of bats-related infections. Residents of a village were recruited by randomly choosing houses from a list obtained from the local head village. Knowledge, attitude and practice were assessed using a 56-items questionnaire. The study recruited 100 respondents. The questionnaire’s Cronbach Alpha score was 0.817. Majority of the respondents were found to have good knowledge (71%), attitude (99%) and practice (64%) relating to bat-related infection. There was a weak positive correlation between knowledge and practice towards bat-related infections among residents of the study population. Majority (80%) of respondents did not aware that bats can cause rabies, and 84% did not know about rabies vaccination. The result of this pilot study provides a limited but valuable insight into bat-related infection. Overall, respondents had good knowledge, attitude and practice scores towards bats-related infection. However, more awareness is needed to key areas lacking such as in educating awareness about rabies in bats.